(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2010)
Transmission-loss is an inherent nature of power system. Determination of transmission losses for the purposes of billing in various interconnected trans-actions is an important issue to be solved exactly. Loss allocation is a procedure for subdividing the system transmission losses into fractions, the cost of which becomes the responsibility of network users. This paper focuses on transmission loss allocation procedures and provides a detailed comparison of some alternative algorithms: viz. 1) Incremental loss allocation, 2) A proportional allocation, 3) Preliminary loss allocation and 4) A direct methodology for loss allocation. A case study based on a 6-bus model power system has been provided. Finally conclusions and recommendations have been stated. Key words: Transmission loss allocation, DC optimal power flow, Deregulated power market, Loss coefficient matrix, Non-volatile procedure. DOI: 10.3329/bjsir.v44i3.4401 Bangladesh J. Sci. Ind. Res. 44(3),289-296, 2009